1991
DOI: 10.1042/bj2800099
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of non-esterified fatty acid and insulin in control of triacylglycerol secretion by Hep G2 cells

Abstract: The role of insulin in the regulation of plasma triacylglycerol is poorly understood. Conflicting actions of insulin on rat liver cells have been reported, insulin inhibiting triacylglycerol secretion in short incubations (less than 24 h) and stimulating triacylglycerol secretion in longer incubations (48-72 h). The present study was undertaken to examine regulation of triacylglycerol secretion by insulin and investigate the interaction between insulin and non-esterified fatty acid over 72 h in human hepatobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(35 citation statements)
references
References 44 publications
3
31
0
1
Order By: Relevance
“…Thus, the NEFA effects on the postprandial metabolism of large TRLs appear to be not solely a consequence of the degree of insulin sensitivity of the individual person. The rate of hepatic VLDL secretion is strongly dependent on the NEFA supply [21]. Failure to suppress the NEFA supply to the liver in the postprandial state could lead to sustained VLDL production and impaired clearance of postprandial TRLs through competition of the large VLDLs with chylomicrons and large chylomicron remnants for hydrolysis by LPL.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the NEFA effects on the postprandial metabolism of large TRLs appear to be not solely a consequence of the degree of insulin sensitivity of the individual person. The rate of hepatic VLDL secretion is strongly dependent on the NEFA supply [21]. Failure to suppress the NEFA supply to the liver in the postprandial state could lead to sustained VLDL production and impaired clearance of postprandial TRLs through competition of the large VLDLs with chylomicrons and large chylomicron remnants for hydrolysis by LPL.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, whereas experiments conducted with isolated perfused rat liver showed that insulin stimulates both synthesis and secretion of TAG [136,137], many subsequent studies conducted on cultured hepatocytes have found that insulin, although promoting synthesis of TAG, inhibits its secretion [6,8,133,138,139]. The reasons for this discrepancy between the two sets of data may reside in the use of different experimental systems (perfused liver, cultured cells) and in the choice of the precise perfusion or culture conditions, by different laboratories.…”
Section: Experimental Observations For a Role Of Insulin In Tag Secrementioning
confidence: 98%
“…Culture of hepatocytes with insulin for 6-48 h results in the inhibition of secretion, whereas more prolonged culture (up to 72 h) results in stimulation of secretion (over a diminishing control value) [142][143][144]. Although this phenomenon has not always been observed [6,145], it has been interpreted as indicating that insulin acts acutely on the liver to inhibit TAG secretion, whereas, when the liver is chronically exposed to high levels of insulin, it becomes resistant to the hormone and the effect is lost. Consequently, it has been suggested that acute exposure of the liver to surges in portal insulin concentration (such as would occur during the prandial period) would result in the inhibition of TAG secretion, whereas more prolonged exposure of the liver to hyperinsulinaemic conditions (e.g.…”
Section: Experimental Observations For a Role Of Insulin In Tag Secrementioning
confidence: 99%
See 1 more Smart Citation
“…Or, des études in vitro et chez l'animal ont également montré que l'acide oléique augmente la production et la sécrétion hépatique des triglycérides associés à l'apo B, sous forme de lipoprotéines de type VLDL riches en triglycérides (TGRL) [25][26][27][28][29][30][31]. D'autre part, si l'apport en acide linoléique est trop faible, l'expression minimale du LDL-récepteur pourrait limiter la dégradation post-traductionnelle des apo-B nouvellement sécrétées [32].…”
unclassified